2021
DOI: 10.1088/1674-1056/ac2d1b
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of persistent photoconductivity in high gain Ga2O3 Schottky photodetectors*

Abstract: The defect-related photoconductivity gain and persistent photoconductivity (PPC) observed in Ga2O3 Schottky photodetectors lead to a contradiction between high responsivity and fast recovery speed. In this work, a metal–semiconductor–metal (MSM) Schottky photodetector, a unidirectional Schottky photodetector, and a photoconductor were constructed on Ga2O3 films. The MSM Schottky devices have high gain (> 13) and high responsivity (> 2.5 A/W) at 230–250 nm, as well as slow recovery speed caused by PPC. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…For the log scale of the current spectrum shown in Figure c, a long tail can be observed after the peak response up to λ = 1100 nm, which could be attributed to the persistent photoconductivity (PPC) that commonly exists in Ga 2 O 3 PDs. This PPC effect, which results from the oxygen vacancies-related traps, could reduce the PD response speed and increase the PD recovery time during the process of trapping and releasing photogenerated electrons in the trapping center. , For example, for a 1 V bias, the currents at λ = 250 and 1100 nm are about 4.3 × 10 –7 and 5.4 × 10 –14 A, respectively. The current at λ = 1100 nm is higher than the I dark (=4.4 × 10 –14 A) measured without illumination.…”
Section: Resultsmentioning
confidence: 99%
“…For the log scale of the current spectrum shown in Figure c, a long tail can be observed after the peak response up to λ = 1100 nm, which could be attributed to the persistent photoconductivity (PPC) that commonly exists in Ga 2 O 3 PDs. This PPC effect, which results from the oxygen vacancies-related traps, could reduce the PD response speed and increase the PD recovery time during the process of trapping and releasing photogenerated electrons in the trapping center. , For example, for a 1 V bias, the currents at λ = 250 and 1100 nm are about 4.3 × 10 –7 and 5.4 × 10 –14 A, respectively. The current at λ = 1100 nm is higher than the I dark (=4.4 × 10 –14 A) measured without illumination.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, very large inconsistency of the device parameters is seen in previous Ga 2 O 3 MSM photodetector studies, where the reported optimized t film values vary from 30 to 1000 nm. While such inconsistency is likely attributed to different material qualities in these studies, it is not clear how the material defect affects the DUV photodetection behavior of a Ga 2 O 3 -based MSM photodetector and how to coordinate the device’s parameters for optimized performance. Particularly, a trade-off effect is commonly observed that relies on lattice defects as trap centers to enhance the photocurrent gain, which, however, inevitably compromises the response speed due to the slow detrapping process. In this work, we perform a systematic study to understand how to design the device’s geometric parameters with Ga 2 O 3 characteristics and defects for fabricating high-performance MSM DUV photodetectors. It is discovered that adopting a micrometer thickness rather than a commonly suggested d p simultaneously achieves more than 18-fold enhancement of responsivity and over 100% enhancement of the response speed in ε-Ga 2 O 3 thin-film MSM photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, even after the UV light is turned off, the trapping holes in the TiAu/AlGaN Schottky junction surface are still maintained due to the electric field, causing a persistent leakage current. 43–45…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, even after the UV light is turned off, the trapping holes in the TiAu/AlGaN Schottky junction surface are still maintained due to the electric field, causing a persistent leakage current. [43][44][45] Fig. 6(a)-(b) shows the curves of transient response photocurrent versus time for the Schottky junction-based TiO 2 / AlGaN/GaN heterostructure photodetector under 274 nm UV illumination with a light intensity of 504 mW cm À2 at negative bias V = À1.5 V and V = À4 V. The UV light was kept on and off for 50 s each.…”
Section: Resultsmentioning
confidence: 99%